Strategi Pengembangan Wisata Pasir Putih dalam Meningkatkan Jumlah Wisatawan di Desa Dalegan Panceng Gresik - Abdullah Zawawi; Diyanatus Siyadah (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2022)
The type of research used in this study is a type of qualitative research. Qualitative research is a study in which the data is expressed in verbal form and is analyzed without using statistics. The results of the research analysis can be concluded that in terms of the development strategy implemented by the Tourism Awareness Group (Pokdarwis) Pasir Putih Dalegan Tourism has a good plan to increase visitors every month. With a special development strategy, namely professional management, it is absolutely essential in a business and business, because if the management is good, it will be easier for others to adjust. Meanwhile, the obstacles in the process of developing the Pasir Putih Dalegan Tourism Object include: The existence of the Covid-19 pandemic which is quite disturbing and has caused the Indonesian people's economy to decline drastically, weather conditions are very difficult to predict, many village people themselves are not aware of the importance of protecting each other's objects. own tourism, unable to manage finances professionally because the Pasir Putih tourist attraction belongs to the village and not to individuals, low public knowledge about tourism and the benefits of tourism, lack of historical knowledge of tour guides to tell historical sites and low mastery of foreign languages ​​by tour guides, such as China, England and others, visitors do not comply with existing regulations.